Vegetation Configuration Effects on Microclimate and PM2.5 Concentrations: A Case Study of High-Rise Residential Complexes in Northern China - Lina Yang; Xu Li; Daranee Jareemit; Jiying Liu (Atmosphere, 2025)
While urban greenery is known to regulate microclimates and reduce air pollution, its integrated effects remain insufficiently quantified. Through field monitoring and ENVI-met 5.1 modeling of high-rise residential areas in Jinan, the results demonstrate that: (1) vegetation exhibits distinct spatial impacts in air-quality impacts, reducing roadside PM2.5 by 26.63 μg/m3 while increasing building-adjacent levels by 17.5 μg/m3; (2) shrubs outperformed trees in PM2.5 reduction (up to 65.34%), particularly when planted in inner rows, whereas tree crown morphology and spacing showed negligible effects; (3) densely spaced columnar trees optimize cooling, reducing Ta by 3–4.8 °C and the physiological equivalent temperature (PET*) by 8–12.8 °C, while planting trees on the outer row and shrubs on the inner row best balanced thermal and air-quality improvements; (4) each 1 m2/m3 leaf area density (LAD) increase yields thermal benefits (ΔTa = −1.07 °C, ΔPET* = −1.93 °C) but elevates PM2.5 by 4.32 μg/m3. These findings provide evidence-based vegetation design strategies for sustainable urban planning.